Priority Diseases, Sustained Response and SDG3.3 - Fingani Annie Mphande (Sustainable development goals series, 2023)
Priority diseases are those designated by WHO as having potential to cause a public health emergency. As such effective countermeasures against these diseases are crucial both at National and global level. The list of priority diseases is updated regularly by WHO. The diseases are rated critical, high, and medium priority and they range from bacterial, viral and fungal pathogens. The fungal pathogen priority list was compiled with a focus on the invasive diseases, limited diagnostics and treatment, and antifungal resistance. However bacterial priority diseases have been ranked according to their antibiotic resistance. Over 700,000 deaths annually have been attributed to drug resistant bacteria. The ability of viruses to spillover from animals to humans and their ability to cause disease in humans is a public health threat globally. In the past decades emerging and re-emerging diseases from viral pathogens of animal origins have been reported. The lack of treatment and vaccines for most viral priority diseases makes these diseases public health threats globally.
Keywords: Zoonotic diseases and public health; Animal Disease Management and Epidemiology; Viral Infections and Vectors